Static versus dynamic medical images: The role of cue utilization in diagnostic performance. Issue 5 (10th August 2021) - Carrigan, Ann J.; Stoodley, Paul; Ng, Kenny; Moerel, Denise; Wiggins, Mark W.
Summary: Echocardiographers can detect abnormalities accurately and rapidly from dynamic images. This is likely due to the application of cue‐based associations resident in memory, a process known as cue utilization. This study investigated whether cue utilization is associated with the ability to apply within‐domain capabilities (dynamic) to more degraded images (static). Fifty‐eight echocardiographers completed the echocardiography edition of the Expert Intensive Skills Evaluation 2.0 (EXPERTise 2.0) to establish behavioral indicators of within‐domain cue utilization. They also completed an abnormality detection and categorization task that comprised briefly presented static and moving images (50% abnormal). Behaviors consistent with higher cue utilization were associated with greater accuracy in detecting both static and dynamic images but not for categorization. This study provides important information about how experts who have the capacity to utilize cue‐based strategies can rapidly and accurately detect abnormalities from domain‐specific stimuli and generalize their skills to more challenging stimuli.